The Admirable Castle: David and his Court in the English Psalter of the Queriniana di Brescia Library - Zonno, Sabina (Eikón / Imago, 2015)
This essay focuses on a magnificent but little-known fourteenth-century English Psalter now in the Biblioteca Queriniana in Brescia, Italy. It is a lavishly illuminated manuscript produced in East Anglia between about 1320 and 1330. The article analyses in detail its peculiarities, the significant feasts in the calendar of Sarum use and the necrological notes added, the iconography, iconology, and style of the decoration. Of particular interest is the unconventional miniature opening the book and depicting King David in a perfectly courtly milieu. The role of the castle as the place of the opposition between virtue and vice is investigated here, and the exploration of the possible secular and religious symbols coexisting in this image has revealed a complex interplay of meanings from diverse textual and visual traditions shown for the first time in my research.